The Psychiatric-Religious Condition of Educated Homosexual Community In Islamic Campus - Azam Syukur Rahmatullah (Soshum: Jurnal Sosial dan Humaniora, 2020)
This research reveals the spiritual-psychological conditions of homosexual students on the Islamic campus of Yogyakarta, Indonesia. The researcher had interviewed four homosexuals from two Islamic based campuses in Yogyakarta. Two respondents came from the Islamic campus A, both of them worshiped, and two respondents were from the Islamic campus B, the two respondents also worshiped. The results of the study stated that these four homosexuals experienced the hesitation of religious spirit, in which one side they continued to carry out Islamic-based campus rules such as prayer, fasting, reading the Qur'an, halaqah, Islamic studies on campus, but on the other hand, the homosexual soul possessed is not easily removed. In the end, they experience "cognitive dissonance" that shows their feelings of discomfort due to conflicting attitudes, thoughts, and behaviors between mind and action. The results of other studies are indicated by the existence of anxiety and fear if God is angry. This is because they worship but still having sex with same-sex. However, these four respondents stated that they could not do anything, and continued to live a life that must be lived.